Short Communication: Growth of seaweed Eucheuma cottonii in multi trophic sea farming systems at Gerupuk Bay, Central Lombok, Indonesia - SUKIMAN SUKIMAN; FATURRAHMAN FATURRAHMAN; IMMY SUCI ROHYANI; HILMAN AHYADI (Smujo International, 2014)
Abstract. Sukiman, Faturrahman, Rohyani IS, Ahyadi H. 2014. Growth of seaweed Eucheuma cottonii in multi trophic sea farming systems at Gerupuk Bay, Central Lombok, Indonesia. Nusantara Bioscience 6: 82-85. Eucheuma cottonii is a seaweed commodity that has a high economic value because it contains compounds used as raw materials for industries. Various methods of seaweed farming have been developed, one of which is a system of cultivation Multi Trophic Sea Farming. This study aimed to analyze the growth of E. cottonii by observing the production of biomass in four trophic combinations in the system Multi Trophic Sea Farming. The study was conducted in the area of the marine aquaculture Gerupuk bay, Central Lombok, Indonesia. Experiments were performed on four plots cages with trophic combination treatment as follows: K1 (E. cottonii-lobster-abalone), K2 (E. cottonii-abalone-red carp), K3 (E. cottonii-abalone-grouper), and K4 (E. cottonii-abalone-pomfret fish). Seedling of E. cottonii weighing 50 g was tied to a rope and placed at a depth of 5 cm, 50 cm, 100 cm, and 150 cm. Measurement of biomass production was done every ten days until the thirtieth day. The highest biomass production of E. cottonii was obtained in K3 trophic combination (E. cottonii-abalone-grouper fish) with a depth of seedlings of 5 cm. The combination of K3 trophic is recommended for cultivation of seaweed in the MTSF system.